In situ modifications of bacterial cellulose film with pandanus amaryllifolius extract for heavy metal removal - Pa’e, Norhayati (2015)
Bacterial cellulose produced from the fermentation of Acetobacter xylinum present a high hydrophilicity and mechanical strength. These properties bring opportunities for the development of high quality paper, film and membrane. The morphology and properties of BC can be altered during the fermentation process. The in situ modifications were done by the addition of additives not specifically required for growth of the bacteria in the fermentation medium. Therefore, active materials can be incorporated into bacterial cellulose films for different applications. In this research, the pandan extract was added to the fermentation medium to produce Bacterial Cellulose-Pandan film. Pandan extract containing pyrroline that consists of cyclic nitrogen (-N=) and ketone, two functional groups that are responsible in metals biosorption. Different concentrations of extract were used to examine their impact on the cellulose production. Then, the films produced were tested with synthetic wastewater containing chromium VI to determine the heavy metal removal percentage. The result shows that increased concentration of pandan extract led to the increased of cellulose yield with proportional removal of heavy metal. In conclusion, in situ modifications during the fermentation process were successfully incorporated pandan extract into the bacterial cellulose fibrils. Hence, the combination of both properties could be used for the development of heavy metal removal materials in wastewater treatment.